2015
DOI: 10.1186/s40608-015-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of the zinc transporter ZIP14 (SLC39a14) is affected by weight loss and metabolic status and associates with PPARγ in human adipose tissue and 3T3-L1 pre-adipocytes

Abstract: BackgroundThe expansion and function of adipose tissue are important during the development of insulin resistance and inflammation in obesity. Zinc dyshomeostasis is common in obese individuals. In the liver, zinc influx transporter ZIP14, affects proliferation and glucose metabolism but the role of ZIP14 in adipose tissue is still unknown. This study investigates ZIP14 gene expression in human adipose tissue before and after weight loss as well as the regulation of ZIP14 during early adipogenesis.MethodsFourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…For example, in the adipose tissue of Zip14 -KO mice, hypertrophy together with enhanced proinflammatory signaling is observed through activation of nuclear factor-kappaB (NF-κB) and the Janus-activating kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway, and this might contribute to obesity-induced insulin resistance [ 62 ]. Consistent with this idea, Zip14 expression is significantly reduced in obese individuals compared with non-obese individuals, and is increased markedly following weight loss [ 63 ].…”
Section: Zinc Distribution Affects Adipocyte Metabolismmentioning
confidence: 86%
“…For example, in the adipose tissue of Zip14 -KO mice, hypertrophy together with enhanced proinflammatory signaling is observed through activation of nuclear factor-kappaB (NF-κB) and the Janus-activating kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway, and this might contribute to obesity-induced insulin resistance [ 62 ]. Consistent with this idea, Zip14 expression is significantly reduced in obese individuals compared with non-obese individuals, and is increased markedly following weight loss [ 63 ].…”
Section: Zinc Distribution Affects Adipocyte Metabolismmentioning
confidence: 86%
“…It has been revealed that obese patients were characterized by a significantly lower expression of Zip14 in subcutaneous adipose tissue, whereas a 10-week weight loss period significantly increased gene expression. Zip14 expression directly correlated with PPARy expression and HDL-C concentration, although being negatively associated with anthropometric markers of obesity, body fat percentage, HOMA-IR, blood glucose, insulin, and TG levels [ 126 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that SLC39A14, a member of the ZIP protein subfamily, is induced during the early stages of adipogenesis, being associated with increased Zn uptake [ 126 ]. It is also notable that Zip14 regulates inflammatory signaling in adipocyte hypertrophy [ 129 ].…”
Section: Introductionmentioning
confidence: 99%
“… 17 It exists in at least two isoforms that differ from each other in the cation-binding domain. 18 Growing evidence shows the implications of SLC39A14 in various human malignancies. According to the ONCOMINE database, 19 SLC39A14 is indicated to be among the top 1% of genes underexpressed in hepatocellular carcinoma compared to normal liver, which was consistent with the findings of Franklin et al 20 The SLC39A14-exon4B transcript variants were identified as biomarkers of colorectal, gastric, and lung cancers which are known to have an aber-rantly activated WNT-signaling pathway.…”
Section: Discussionmentioning
confidence: 99%